BRAFV600E‐PROTAC versus inhibitors in melanoma cells: Deep transcriptomic characterization - Solomon O. Alhassan; Zakaria Y. Abd Elmageed; Youssef Errami; Guangdi Wang; Joe A. Abi‐Rached; Emad Kandil; Mourad Zerfaoui (Clinical and Translational Medicine)
Abstract Aims This study compares the suppression of Mitogen‐activated protein kinase (MAPK) signalling and early resistance potential between a proteolysis‐targeting chimera (PROTAC) and inhibitors targeting BRAFV600E. Methods We performed a detailed in silico analysis of the transcriptomic landscape of the A375 melanoma cell line treated with a PROTAC and BRAFV600E inhibitors from RNA sequencing data. The study assessed gene dysregulation, MAPK and Phosphoinositide‐3‐kinase (PI3K/AKT) pathway inhibition, and cell survival. Key genes uniquely dysregulated by PROTAC treatment were validated by qPCR. Furthermore, analysis was performed to evaluate dedifferentiation and early resistance signatures to understand melanoma drug‐induced plasticity. Results PROTAC‐treated cells showed significantly lower MAPK pathway activity, strong cell cycle arrest and elevated apoptotic gene expression compared to inhibitor‐treated cells, with no effect on the PI3K/AKT pathway. A high microphtalmia‐associated transcription factor (MITF)/Tyrosine‐Protein Kinase Receptor (AXL) ratio in PROTAC‐treated cells indicated reduced early drug resistance. BRAF degradation induced a melanocytic‐transitory phenotype. Although PROTAC and inhibitor treatments caused overlapping transcriptomic changes, key differences were observed. PROTAC treatment enriched processes such as epithelial‒mesenchymal transition, inflammatory responses, and Tumor necrosis factor‐Alpha (TNF‐α) and IL2/STAT5 signalling. Conclusion PROTAC‐targeting BRAFV600E demonstrates enhanced MAPK suppression, reduced early resistance and distinct transcriptional effects compared to traditional inhibitors. It represents a promising strategy for overcoming resistance in melanoma treatment.